Influence of the addition of pozzolan on the porosity and compressive strength of concrete (LACCEI, 2024)
Abstract-The interaction of concrete with pozzolan is characterized by the chemical reactions between the cement compounds and silica from pozzolan, these reactions generate a change inside the concrete matrix. The objective of the study was to evaluate the influence of pozzolan in the porosity and resistance to compression of concrete. In the experimental phase 48 samples were made with a relation w/c of 0.45 with additions of 0, 10, 15, 20% of pozzolan compression essays (ASTM C39) and the quantity of empty spaces (ASTM C642) essays were carried out. The results were compared to the control samples, finding that in all the cases the resistance to compression determined at 28 days increased in 15, 20 and 13% with respect to the control samples. Additionally, it was determined that the higher values of resistance to compression were obtained with 15% of pozzolan. Regarding the porosity, it was observed that the pozzolan effect is notorious at 56 days, where the values of porosity decreased in all the cases for the pozzolan content of 10, 15 and 20% respectively. From the results obtained it can be concluded that the pozzolan reactions affect the porosity, decreasing it up to 10% after 56 days, and the best effects were found with 15% of pozzolan. Likewise, trough the use of categorical linear regression models it was demonstrated that the porosity significatively and directly influences the resistance to compression obtaining a correlation coefficient R=0.892.